Identifying innovators and early adopters of agricultural technology: A case of wheat varieties in Rajasthan, India - Varshney, Deepak; Joshi, Pramod Kumar; Roy, Devesh (International Food Policy Research Institute, 2019)
The study explores the diffusion process of innovators, early adopters, and late adopters of agricultural technologies. We define innovators, early adopters, and late adopters based on the time taken to adopt improved technology in a well-defined geographic area. The paper is based on a primary survey of 866 wheat farmers conducted in the state of Rajasthan, India. The primary objective of the study is to identify the structural characteristics and information channels for farmers classified as innovators and early adopters. The secondary objective is to present a more disaggregated analysis by assessing the factors that affect the adoption of recent seed varieties. The first objective is based on binary choice modeling, and the second objective relies on the empirical formulation drawn from Besley and Case (1993) that accounts for the dynamic processes related to adoption in the cross-sectional framework.